Threats to oral polio vaccine acceptance in Somalia: Polling in an outbreak. Issue 31 (25th July 2018) - SteelFisher, Gillian K.; Blendon, Robert J.; Haydarov, Rustam; Lodge, William; Caporello, Hannah; Guirguis, Sherine; Anand, Saumya; Birungi, Julianne; Williams, Matthew R.; Ben-Porath, Eran N.; O'Reilly, Denise; Sahm, Christoph
Abstract: Background: Using a survey conducted during the 2013–2014 polio outbreak in Somalia, this study examines attitudinal and knowledge-based threats to oral polio vaccine acceptance and commitment. Findings address a key gap, as most prior research focuses on endemic settings. Methods: Between November 19 and December 21, 2013, we conducted interviews among 2003 caregivers of children under 5 years in select districts at high risk for polio transmission. Within each district, sample was drawn via a multi-stage cluster design with random route household selection. We calculated the percentage of caregivers who could not confirm recent vaccination and those uncommitted to future vaccination. We compared these percentages among caregivers with varying knowledge and attitudes, focusing on variables identified as threats in endemic settings, using controlled and uncontrolled comparisons. We also examined absolute levels of threat variables. Results: Only 10% of caregivers could not confirm recent vaccination, but 32% were uncommitted to future vaccination. Being unvaccinated or uncommitted were related to multiple threat variables. For example, compared with relevant counterparts, caregivers were more likely to be unconfirmed and uncommitted if they did not trust vaccinators "a great deal" (unconfirmed: 9% vs. 2%; uncommitted: 49% vs. 28%), which is also true in endemic settings. Unlike endemic settings, symptom knowledge was related to commitment while rumor awareness was low and unrelated to past acceptance or commitment. Levels of trust and perceptions of OPV effectiveness were high, though perceptions of community support and awareness of logistics were lower. Conclusions: As in endemic settings, outbreak responses will benefit from communications strategies focused on enhancing trust in vaccinators, institutions and the vaccine, alongside making community support visible. Disease facts may help motivate acceptance, and enhanced logistics information may help facilitate caregiver availability at the door. Quelling rumors early may be important to prevent them from becoming threats.